2013
DOI: 10.1007/978-3-642-40352-1_28
|View full text |Cite
|
Sign up to set email alerts
|

A Classification of Industrial Symbiosis Networks: A Focus on Materials and Energy Recovery

Abstract: Abstract. Industrial symbiosis (IS) has gained more attention in the production economics as the pressure on companies increases for the reduction of waste emissions as well as of primary resources consumption. At present, as the number of IS initiatives increases, many issues about its boundaries, such as the entities involved and the resources shared/exchanged, still continue to remain open. A common classification of IS networks does still not exist.Input-output matching is the most significant tool to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This definition has been transposed to industries in which industrial symbiosis "engages traditionally separate entities in a collective approach to competitive advantage involving physical exchange of materials, energy, water, and by-products" (Chertow, 2000). This definition is widely disseminated in the developing industrial ecological environment and research community (Albino et al, 2013). Posteriorly, industrial symbiosis was also identified as "a business opportunity and tool for eco-innovation" (Lombardi and Laybourn, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This definition has been transposed to industries in which industrial symbiosis "engages traditionally separate entities in a collective approach to competitive advantage involving physical exchange of materials, energy, water, and by-products" (Chertow, 2000). This definition is widely disseminated in the developing industrial ecological environment and research community (Albino et al, 2013). Posteriorly, industrial symbiosis was also identified as "a business opportunity and tool for eco-innovation" (Lombardi and Laybourn, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It was also emphasized that "the keys to industrial symbiosis are collaboration and the synergistic possibilities offered by geographic proximity" (Chertow, 2004). There are also studies discussing the ambiguity of the above definition and the space for diversified interpretations of industrial symbiosis (Albino et al, 2013;Golev and Corder, 2012;Lombardi and Laybourn, 2012). Industrial symbiosis in an integrated system can be divided into internal industrial symbiosis and external industrial symbiosis (Zhu et al, 2007).…”
Section: System Boundary and Methods For Co 2 Emission Calculation Inmentioning
confidence: 96%